PERAN PEMBIAYAAN MURABAHAH SEKTOR PRODUKTIF DALAM MENINGKATKAN PENDAPATAN ANGGOTA USAHA MIKRO KECIL DAN MENENGAH (UMKM) BAITUL MAAL WAT TAMWIL (BMT) LANTASIR KOTA KEDIRI - Martalia, Elva; Samsuri, Ali; Mahfudhotin, Mahfudhotin (Reinforce: Journal of Sharia Management, 2024)
Murabahah financing is a sales contract for goods by stating the acquisition price with an agreed profit margin between the buyer and seller. Murabahah financing can be used to help with capital issues for Micro, Small, and Medium Enterprises (MSMEs). This study aims to understand the implementation of productive sector murabahah financing at Baitul Mall Wat Tamwil (BMT) Lantasir in Kediri City and to determine the role of productive sector murabahah financing in improving MSMEs at BMT Lantasir in Kediri City. This study uses a qualitative research method with descriptive analysis, aiming to create a systematic, factual, and accurate description and illustration of the facts and the relationships between the investigated phenomena. This research was conducted using data collection techniques in the form of direct interviews with related parties. The results of this study conclude that the implementation of productive sector murabahah financing at BMT Lantasir in Kediri City includes completing requirements such as (photocopy of husband's/guardian's ID card, collateral documents, and form filling). The murabahah financing is carried out by BMT purchasing the members' needed goods and reselling them to the members with an agreed margin. This is done by BMT Lantasir. The role of productive sector murabahah financing in improving MSMEs has been carried out by adhering to Islamic principles in providing capital loans to the community to develop their businesses and create job opportunities for the surrounding community. This is evidenced by the increased income of MSME actors who received financing compared to before and after receiving financing. Hence, there is a significant increase in sales turnover and income.